Electromagnetic Nondestructive Evaluation (X) - Takahashi, Seiki; Kikuchi, Hiroaki (Studies in applied electromagnetics and mechanics, 2007)
Since the first Electromagnetic Nondestructive Evaluation (ENDE) workshop was held in London 1995, the workshops have contributed to the technical advance in ECT through competition and collaboration. This title focuses on 'Eddy Current Testing' (ECT) to identify cracks in metals and alloys.